2010
DOI: 10.1093/europace/eup413
|View full text |Cite
|
Sign up to set email alerts
|

Device-based impedance measurement is a useful and accurate tool for direct assessment of intrathoracic fluid accumulation in heart failure

Abstract: Changes of Z show a strong inverse correlation with changes of directly measured EVLWI. This allows the application of Z as a measure of intrathoracic fluid status and has the potential to optimize patient care, especially in the context of evolving telemedicine concepts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…For accuracy, is de-embedded to be by subtracting the input parasitic resistor and capacitor from measured . Then, substituting and into (12) can yield as (18) Once is determined, substituting and , which represents the de-embedded reflected resistance of obtained in the measurement mode, into (12) yields (19) Further, substituting given by (18) into (19) simplifies to (20) Finally, subtracting parasitic resistance and from obtained yields…”
Section: B Measuring Inductive Coupling Impedancementioning
confidence: 99%
“…For accuracy, is de-embedded to be by subtracting the input parasitic resistor and capacitor from measured . Then, substituting and into (12) can yield as (18) Once is determined, substituting and , which represents the de-embedded reflected resistance of obtained in the measurement mode, into (12) yields (19) Further, substituting given by (18) into (19) simplifies to (20) Finally, subtracting parasitic resistance and from obtained yields…”
Section: B Measuring Inductive Coupling Impedancementioning
confidence: 99%
“…Besides, very recently, Becher et al [42] have published the results of an animal study in which implant-based impedance showed a strong inverse correlation with changes of directly measured intrathoracic fluid accumulation.…”
Section: Clinical Impact Of Hemodynamic Sensorsmentioning
confidence: 99%
“…Currently, the techniques for tracking decompensation or general fluid accumulation in HF patients includes daily measures of weight or other more complicated measures such as chest X-ray or CT scans of the lungs, however, it is expensive and/or the diagnostic sensitivity of these techniques is not high (Mahdyoon et al, 1989; Becher et al, 2010; Gupta et al, 2012). In addition, B-type natriuretic peptide (BNP) level, which often increases when HF symptoms are exacerbated, is still in question (Lewin et al, 2005; Becher et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, B-type natriuretic peptide (BNP) level, which often increases when HF symptoms are exacerbated, is still in question (Lewin et al, 2005; Becher et al, 2010). As fluid accumulation is one of the major predictors of decompensative events associated with HF, it is very important to develop more sensitive and cost-effective techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation